Ionizing radiation enhances IL-6 and IL-8 production by human endothelial cells - A. Van Der Meeren; J.-M. Bertho; M. Vandamme; M.-H. Gaugler (Hindawi Limited, 1997)
Irradiation exposure is known to induce an inflammatory reaction. Endothelial cells play a crucial role both in the inflammatory process and in radiation damage. Therefore, supernatants and cell lysates of 60Co-irradiated human umbilical vein endothelial cells (HUVEC) have been assessed for the presence of pro-inflammatory cytokines. After gamma irradiation, interleukin (IL)-1α, IL-1β and tumor necrosis factor (TNF)-α remained undetectable in both cell supernatants and cell lysates. However, a dose-dependent increase in the production of IL-6 and IL-8 has been demonstrated up to 6 days after exposure. These data indicate that the pro-inflammatory cytokines IL-6 and IL-8 may be involved in the inflammatory response of vascular endothelium induced by exposure to ionizing radiation.